Suraya's Traditional Rempeyek / Suraya Mohamad Mahmod Yap - Mohamad Mahmod Yap, Suraya (2017)
Today's Malaysian food industry has been a very popular market and high demand for the past many years. My current business plan is to be the one manufacturing and production of rempeyek. Nowadays, everyone can make rempeyek but does it taste good? crispy? Thus, my mission is to continue our special secret recipes from our grandmother. Suraya's Traditional Rempeyek is a new company that operated in Ipoh, Perak. We started our business since 2000 only for our friends and families. At that time, the production of our rempek just as much as 10-15 jars a month. After we are getting positive feedback from them, we are started to sell in open market around 15-30 jars a moths depends on festive season. Until today, we have expanded our business by putting our rempeyek at petrol stations (around Ipoh) and dropship this project helped us a lot in this regard. This project also we can learn about how to sell our product to customers. Using Facebook application, customer can easily informed and understand